COMMERCIAL CUT OF CROSSBREED LANDRACE PORK CARCASS GIVEN PROTEIN CONCENTRATE CHICKEN LIVESTOCK WASTE - I P.G. K., Wirakusuma; Ariana, I N. T.; Miwada, I N. S. (Jurnal Peternakan Tropika, 2024)
This study aimed to determine commercial crossbreed landrace pig carcasses given chicken farm waste protein concentrate (KPLA) on landrace crossbreed pig rations. The pigs used are landrace crosses of the Finisher phase. The design used in study was completely randomized design (CRD) with three treatments and each treatment was repeated four times. The three treatments consisted of A: Ration without KPLA (Control), B: Ration with 12% KPLA, and C: Ration with 24% KPLA. The variables observed in this study were slaughter weight, carcass weight and percentage, carcass length, and percentage of carcass commercial pieces. The results showed that substitution of commercial feed with KPLA was significantly different (P<0.05) to carcass percentage, carcass length, carcass weight, loin percentage and belly percentage, while not significantly different (P>0.05) to slaughter weight, percentage of jowl, boston shoulder, picnic shoulder and ham. Based on the results of this study it can be concluded that substitution of commercial concentrate with 12% protein concentrate from chicken farming waste (KPLA) gave the same results in slaughter weight, carcass weight, percentage of carcass, length of carcass, and percentage of commercial carcass pieces, while substitution of commercial concentrate with 24% KPLA reduced carcass weight, carcass percentage, carcass length and loin percentage, but increased belly percentage.